Pemanfaatan Teknologi Sebagai Sumber Informasi Bagi Mahasiswa Dalam Menyelesaikan Tugas - Nur Afinni, Ummi; Panggabean, Alimatusakdia; Syahputri, Nidi; Fadhila, Puan (IAI Nasional Laa Roiba Bogor, 2024)
In current technological developments the use of technology as a source of information for students is very helpful, especially Google Scholar in helping find scientific work in the form of abstract articles and so on. This study aims to examine the use of technology as a source of information and the use of Google Scholar in helping to complete assignments. The research method used is descriptive qualitative method. With data collection techniques through interviews for information data collection carried out by researchers by asking questions to informants. The results of the analysis show that the use of technology as a source of information, especially the use of Google Scholar in completing tasks is very helpful in making scientific work, because it provides academic literature or various scientific works and various scientific disciplines in the form of abstract books, articles and so on. Keywords: Technology, Information, Google Scholar